Implementación del programa de observadores de seguridad "Mineros cuidando Mineros" en la unidad Minera San Rafael - Puno - Quispe Cruz, Wilson (2018)
This research work entitled "IMPLEMENTATION OF THE OBSERVATORY PROGRAM OF SAFETY OBSERVERS "MINERS CARING FOR MINERS "AT THE SAN RAFAEL MINE - PUNO", was carried out at the facilities of MINSUR SA Company, this mine produces Tin concentrates, it’s located in the district of Antauta, province of Melgar, and department of Puno, and at an altitude of 4200 meters above sea level. Through the implementation of the Program of Safety Observers "Miners Caring for Miners", incentives were established to transform unsafe behaviors into safe behaviors Field tests were done keeping in mind the work items which control the risky behaviors, so it was necessary to evaluate the variables: "Miners tending miners Program" and the reduction of accidents in the first half of 2017; The tests were applied in two steps, Diagnosis, which helped to see in the field and find a real way the unsafe and safe behavior of the personnel; Then the ending step, has permitted to recognize the goals reached by the objectives of this paper, which was to decrease the number of accidents and incidents in the first half of 2017. This work brings conclusions made after an evaluation of the results gotten in the field tests. One of the main causes of incidents and accidents is human behavior, therefore it is necessary to control this factor, and this work proposes a specific plan for San Rafael mine. Thus we have as Recommendations, to continue with the Program of Observers of Security "Miners taking care of miners" and establish economic stimuli and of recognition.